Europeanising Greens in an evolving European democracy: roles and limitations - Huan, Qingzhi (2006)
Abstract: "Built upon a methodological assumption that conventional theory of democracy and party politics after some modifications can be applied to analysing the EU politics, this article offers a case study of the European Green Party (EGP) by focusing on its three aspects-political programme, organisational structure and political participation. As the main conclusion, the author argues that the EGP has evolved into a Euro-party by the end of the EP's fifth term in terms of certain standards, yet its roles as a system-maker for the EU's democratic transformation are still very limited." (author's abstract)